Respuesta :
Answer:
a) [tex]-5x^{2}+3x+27[/tex]
b) [tex]-5x^{2}+3x+9[/tex]
Step-by-step explanation:
a) Let the required polynomial be p(x).
We have the relation, [tex]5x^{2}-3x-9[/tex] + p(x) = 18
i.e. p(x) = 18 [tex]-5x^{2}+3x+9[/tex]
i.e. p(x) = [tex]-5x^{2}+3x+27[/tex]
b) Let the required polynomial be q(x).
We have the relation, [tex]5x^{2}-3x-9[/tex] + q(x) = 0
i.e. q(x) = 0 [tex]-5x^{2}+3x+9[/tex]
i.e. q(x) = [tex]-5x^{2}+3x+9[/tex]
Answer:
(a) [tex]-5x^2+3x+27[/tex]
(b) [tex]-5x^2+3x+9[/tex]
Step-by-step explanation:
(a)
Let the polynomial be Q(x).
Given polynomial P(x) = [tex]5x^2-3x-9[/tex]
As per the given statement: A polynomial(Q(x)) which, when added to the polynomial [tex]5x^2-3x-9[/tex], is equivalent to 18.
[tex]P(x)+Q(x) = 18[/tex]
[tex]5x^2-3x-9 +Q(x) = 18[/tex]
⇒[tex]Q(x) = 18 -(5x^2-3x-9)[/tex]
or
[tex]Q(x) = 18 -5x^2+3x+9[/tex]
Simplify:
[tex]Q(x) =-5x^2+3x+27[/tex]
Therefore, the polynomial is, [tex]-5x^2+3x+27[/tex]
Check:
[tex]P(x)+Q(x)[/tex] = [tex]5x^2-3x-9 +(-5x^2+3x+27)[/tex]
= [tex]5x^2-3x-9 -5x^2 +3x+27[/tex]
= 18
(b)
Let the polynomial be Q(x).
Given polynomial P(x) = [tex]5x^2-3x-9[/tex]
As per the given statement: A polynomial(Q(x)) which, when added to the polynomial [tex]5x^2-3x-9[/tex], is equivalent to 0.
[tex]P(x)+Q(x) = 0[/tex]
[tex]P(x) = -Q(x)[/tex]
⇒[tex]Q(x) = -(5x^2-3x-9)[/tex]
or
[tex]Q(x) = -5x^2+3x+9[/tex]
Therefore, the polynomial is, [tex]-5x^2+3x+9[/tex]
Check:
[tex]P(x)+Q(x)[/tex]=[tex]5x^2-3x-9 +(-5x^2+3x+9)[/tex]
= [tex]5x^2-3x-9-5x^2 +3x+9[/tex]
= 0